The Implementation of Teaching at the Right Level (TARL) Approach in Teaching Reading at Senior High School - Nahdiatul Najah; Baso Jabu; Muhammad Basri (International Journal of Language, Education, and Literature, 2024)
The teaching at the Right Level (TaRL) approach has been increasingly recognized as a powerful strategy to enhance reading comprehension and motivation among students. This article explores the implementation of TaRL in teaching reading at senior high schools, focusing on the experiences of teachers and students in SMA Negeri 3 Makassar. The study aims to identify how teachers implement TaRL, their perceptions of the approach, and its impact on student learning. The research methodology involves a qualitative design, with data collected through interviews and documentation. The findings reveal that TaRL enhances reading comprehension and improves student motivation, but challenges such as teacher training and resource allocation are identified. The study concludes that TaRL is impactful in addressing the diverse needs of students and recommends its adoption in senior high schools.